TINGKAH LAKU MAKAN IKAN KERAPU MACAN (Epinephelus fuscoguttatus) TERHADAP PERBEDAAN UMPAN (SKALA LABORATORIUM) - Aristi Dian Purnama Fitri (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
Fish eating behavior is  the  result  of the  interaction of several senses in  fish depend on the habitat  and the  effect produced by  the food.  Bait as  food is  one  form  of the  stimulus in  the form of physical / chemical that can provide a response to fish of certain fish for fishing. This study describes the eating behavior of Tiger Krapu Fish (Epinephelus fuscogutattus) by using natural bait during  the  day and  evening.  Parameters that observed are  patterns  of eating behavior and eating response time of Krapu Fish. The research method used is descriptive and experiment  on laboratory scale.  The  Observation  of behavioral responses by  using  a    light condition  pond and the  dark  condition  pond.  Bait that  used  was a  natural bait,  including shrimp,  fish,  and sea  urchins.  Stages  of eating behavior observations including  arousal, searching,  and finding phase.  The  behavior of  Krapu fish  to  bait  in bright  conditions is  not different to arousal phase and finding phase. The behaviour of Krapu fish in dark condition to natural bait (sea urchin gonadal, shrimp, and fish) is nit different to arousal phase, searching phase, and finding phase.Keywords : eating behaviour, epinephelus fuscoguttatus), bait